Analisis Etika Liberasi dalam Cerpen Kompas Tahun 2023: Tinjauan Sastra Profetik Kuntowijoyo - Prawoto Prawoto; Suyatno Suyatno; Resdianto Permata Raharjo (Jurnal Ragam Pengabdian, 2026)
This study aims to describe the manifestation of liberative ethics in selected short stories published in the 2023 edition of the Kompas daily, through the perspective of prophetic literature as formulated by Kuntowijoyo. Liberative ethics is understood as an effort to emancipate human beings from alienation and oppressive, unjust social structures. Employing a descriptive qualitative method and content analysis techniques, this study examines five short stories that embody a spirit of resistance against social, economic, and cultural constraints. The findings reveal that liberative ethics in the 2023 Kompas short stories is reflected in the characters’ courage to challenge injustice and their efforts to break free from hegemonic power structures that restrict human dignity. This study concludes that prophetic literature remains relevant as a critical instrument for social critique within contemporary Indonesian literary discourse